Benzoindolium–triarylborane conjugates: a ratiometric fluorescent chemodosimeter for the detection of cyanide ions in aqueous medium. Issue 12 (15th December 2015) - Arivazhagan, C.; Borthakur, Rosmita; Jagan, R.; Ghosh, Sundargopal
Abstract : A new ratiometric fluorescent chemodosimeter has been synthesized and characterized that exhibits high selectivity and sensitivity toward CN − ions in aqueous medium. Abstract : Based on benzo[ e ]indolium and dimesitylborylbenzaldehyde a new ratiometric fluorescent chemodosimeter, C41 H43 BIN (3 ) has been synthesized and characterized by 1 H, 13 C NMR spectroscopy, mass spectrometry and single crystal X-ray crystallography. Probe3 was found to be highly selective and sensitive toward cyanide (CN − ) ions in aqueous medium even in the presence of other competing anions like F −, Cl −, Br −, I −, H2 PO4 −, HCO3 − and AcO − . The detection limit was calculated to be 7.1 × 10 −9 M, which is much lower than the maximum permissable concentration in drinking water (1.9 μM) set by the World Health Organization (WHO). In addition, the response time of the probe for CN − is less than 5 seconds. The mechanism is based on a nucleophilic addition reaction of cyanide ions at the polarized [>CN<] + bond of the benzoindolium group thereby blocking the pi-conjugation between the benzoindolium and triarylborane moiety. This was further confirmed by 1 H NMR titration, ESI-MS studies and DFT calculations.